Actinomyces israelii May Produce Vulvar Lesions Suspicious for Malignancy - Jennifer Y. McElroy; Marsha E. Gorens; Lisa N. Jackson; Danielle Stigger; Teresa Becker; Eyal Sheiner (Hindawi Limited, 2006)
Background. We present a case of Actinomyces israelii causing vulvar mass suspicious for malignancy in a postmenopausal woman. Case. A 60 year-old woman presented due to a firm, nonmobile, 10 cm vulvar mass, which had been rapidly enlarging for 5 months. The mass was painful, with localized pruritus and sinus tracts oozing of serosanguinous fluid. Biopsy and cultures revealed a ruptured epidermal inclusion cyst containing granulation tissue and Actinomyces israelii. Conclusion. Actinomyces israelii may produce vulvar lesions that are suspicious for malignancy. Thus, biopsies and cultures are both mandatory while evaluating vulvar masses suspicious for malignancy.